Enhanced terahertz shielding by adding rare Ag nanoparticles to Ti3C2Tx MXene fiber membranes. (22nd July 2021) - Zou, Qi; Shi, Chaofan; Liu, Bo; Liu, Dejun; Cao, Duo; Liu, Feng; Zhang, Yi; Shi, Wangzhou
Abstract: Polyacrylonitrile/Ti3 C2 T x MXene/silver nanoparticles fiber membranes with different silver nanoparticles contents and thickness of porous structure have been successfully prepared by electrospinning. Through the measurement of terahertz time domain spectrum, the shielding effect of the fiber membrane with 1% silver nanoparticles content can reach up to 12 dB. Moreover, the thickness of the spinning fiber membranes is controlled by adjusting the spinning time, so as to better analyze the influence of the thickness of the shielding performance in terahertz band. We attribute this excellent phenomenon to porous structure of the spun fiber membrane and combination of Ti3 C2 T x MXene with few-layers and silver nanoparticles to increase the absorption and conductivity of the fiber membrane, thereby enhancing the shielding effect in terahertz range. Meanwhile, the prepared polyacrylonitrile/Ti3 C2 T x MXene/silver nanoparticles fiber membranes show good stability and little change in terahertz shielding effect after high temperature annealing. This may provide potential ideas about the development of high-performance terahertz shielding materials, which are of great significance of terahertz electromagnetic shielding.